Smart City Integration in Azerbaijan: how to make it sustainable with the possible challenges in the country context? - Aliyev, Eldar; Velieva, Phargane; Ibrahimova, Ilaha (ADA University, 2022)
There are several concepts for the smart city development. However, its management is considered as a crucial primary part of the overall smart city projects. Governance of the smart urban models includes many different aspects such as e-governments, smart decision making processes, and coordination. Thus, smart management consist of the digital communication tools, strong partnership, and cooperation, as well as the quality services provided to the city citizens. The administration of smart cities is one of the most important principles in assuring their development. Smart city management encompasses ideas like smart government, smart decision-making, smart administration, and smart coordination. As a result, smart management is a system that includes the use of data and knowledge tools in administration, the building of stakeholder relationships, joint action, as well as the daily routines of city residents and businesses. The goal of this capstone project is to investigate the challenges of Smart City Integration in Azerbaijan. Due to financial constraints, lack of awareness amongst citizens, and challenges in smart city governance, the country's idea of potential implementation remains mostly undeveloped, according to the report. The report suggests several policy recommendations for each of these issues, including the establishment of a working group to engage in public-private partnership and inviting the other stakeholder to involve in the process, the creation of a dynamic workshop model based on a real-world format that fulfills the requirement for smart city awareness while also boosting the workshop's entertaining aspect, finding partner institutions, governments or cities which are successful in the implementation of the PPP and are willing to share their expertise with Azerbaijan, cooperating with international organizations, development of the online portals for smart city data, and conducting a thorough review of the literature on billboards and posters as a participation strategy in order to discover factors that influence citizens’ acceptance. All options are assessed based on five primary criteria: efficacy, efficiency, equity, feasibility/ implementability, and flexibility/improvability. Secondary data sources were used in the study, as well as semi-structured interviews with experts and citizens on the subject. The analysis and assessments show that in order to develop smart city concept, the government should encourage the establishment of Private-Public partnerships for smart city financing, spread citizens’ awareness of implementing smart city concepts, and establishment of smart city governance concepts that will allow the country to successfully accomplish the goal.
Keywords: Smart City.; Urbanization.; Digital Transformation.; Smart Governance.; Urban Development.; Public and International Affairs